Determinant of Moslem Consumer Purchasing Decisions at Mixue Franchise in Sidoarjo City East Java - Barokatur Rizkiyatul Ula; Novie Andriani Zakariya (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2024)
This study analyzes the factors that influence purchasing decisions in the Sharia market, both partially and simultaneously. Partially, the study examines the influence of price, product variety, taste, and location on purchasing decisions. Simultaneously, research looks at the combined effects of these factors. The method used is quantitative with an associative research model, as well as a purposive sampling technique to select respondents according to Sharia market criteria. The research results show that price (p = 0,011), product variety (p = 0,043), and location (p = 0,018) have a significant effect on purchasing decisions, while taste (p = 0.562) has no significant effect. Overall, all these factors significantly influence purchasing decisions (p = 0,000). These findings emphasize the importance of Sharia principles in pricing, product variety, and location in improving consumer purchasing behavior in Islamic markets.This study analyzes the factors that influence purchasing decisions in the Sharia market, both partially and simultaneously. Partially, the study examines the influence of price, product variety, taste, and location on purchasing decisions. Simultaneously, research looks at the combined effects of these factors. The method used is quantitative with an associative research model, as well as a purposive sampling technique to select respondents according to Sharia market criteria. The research results show that price (p = 0,011), product variety (p = 0,043), and location (p = 0,018) have a significant effect on purchasing decisions, while taste (p = 0.562) has no significant effect. Overall, all these factors significantly influence purchasing decisions (p = 0,000). These findings emphasize the importance of Sharia principles in pricing, product variety, and location in improving consumer purchasing behavior in Islamic markets.